Critical issues in public art content, context, and controversy (Washington Smithsonian Books, 1998)
"In this groundbreaking anthology, twenty-two artists, architects, historians, critics, curators, and philosophers explore the role of public art in creating a national identity, contending that each work can only be understood by analyzing the context in which it is commissioned, built, and received. They emphasize the historical continuum between traditional works such as Mount Rushmore, the Washington Monument, and the New York Public Library lions, in addition to contemporary memorials such as the Vietnam Veterans Memorial and the Names Project AIDS Quilt. They discuss the influence of patronage on form and content, isolate the factors that precipitate controversy, and show how public art overtly and covertly conveys civic values and national culture.Complete with an updated introduction, Critical Issues in Public Art shows how monuments, murals, memorials, and sculptures in public places are complex cultural achievements that must speak to increasingly diverse groups.'' -- Provided by publisher
Keywords: Public art -- United States; Electronic books